The Correlation Between English Learners’ Motivation and Speaking Achievement - Haspia Latauga; Isnaeni Wahab; Nurul Fachrunnisa (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2023)
This research aims to determine the correlation between English learners’ motivation and speaking achievement due to the lack of student motivation, particularly in speaking skills that affect the speaking score. The samples of this study were 19 students taken from the second semester of the English Department at the Muslim University of Maros. The method used was mixed methods with correlational technique. Quantitative data was collected by distributing questionnaires to students using Gardner's Attitude/Motivation Test Battery (AMTB) indicators and the speaking scores taken from the speaking lecturer. Then, qualitative data was collected through semi-structured interviews. In analyzing quantitative data, questionnaires assessed by Likert Scale and speaking scores were analyzed using SPSS, while the qualitative data used Miles and Huberman analysis. The quantitative data results indicate a correlation between the motivation of English learners and speaking achievement, with a score of 0.672. It is considered that the higher the motivation in learning speaking, the better the speaking achievement the students achieve. Students with high motivation will try to follow the learning process intensively compared to those with less motivation. Furthermore, students' extrinsic and intrinsic motivation were analyzed by looking at the AMTB’s Gardner and the results of the interview as well. The data results indicated that students show extrinsic motivation more than intrinsic motivation in their speaking achievement.